Anxiety and depression mediate the health-related quality of life differently in patients with cardiovascular disease and stroke-preliminary report of the Yilan study: a population-based community health survey. - Nai-Wei Hsu (Public Library of Science (PLoS), 2014)
Background Cardiovascular disease and stroke have emerged as substantial and growing health challenges to populations around the world. Besides for the survival and medical prognosis, how to improve the health-related quality of life (HRQoL) might also become one of the goals of treatment programs. There are multiple factors that influence HRQol, including comorbidity, mental function and lifestyle. However, substantial research and investigation have still not clarified these underlying pathways, which merit further attention. The purpose of this study was to determine how psychological factors affect the link between cardiovascular disease and stroke with HRQoL. Methods and result A total of 1,285 elder subjects at least 65 years of age (47.2% male) were enrolled. The mental function and HRQol of each patient was then measured using the Hospital Anxiety and Depression Scale and Short Form-12. After multiple regression analysis, anxiety, depression, cardiovascular disease, stroke, education level and age were shown to be associated with both mental component score (MCS) and physical component score (PCS). In the mediation analysis using the SPSS macro provided by Preacher and Hayes, cardiovascular disease and stroke affected HRQoL via anxiety and depression, respectively. Conclusions These results suggest that cardiovascular disease and stroke have negative impacts on patient MCS and PCS through different underlying pathways. Cardiovascular disease influences the HRQoL both directly and indirectly with the mediation of anxiety, and stroke influences the HRQoL by way of depression. These findings support the proposition that different combinations of both physical and psychological support are necessary to best manage these diseases.